Payments for environmental services (PES) schemes supporting sustainable agricultural practices in the US, EU and UK - Hettiarachchi, Upeksha; Zhang, Wei (CGIAR System Organization, 2025)
The purpose of this note is to examine the experience of using payments for ecosystem services (PES) to support the use of sustainable agricultural practices, focusing on documented cases from the US, EU, and UK. The note describes the programs’ goals and evolution, eligibility and targeting criteria, payout modalities, monitoring and evaluation, and outcomes.